Teaching Students to Engage with Evidence: An Evaluation of Structured Writing and Classroom Discussion Strategies. Issue 1 (2nd January 2017) - Blings, Steffen; Maxey, Sarah
ABSTRACT: In their transition to college, students often struggle to identify and make connections between the main arguments, evidence, and empirical findings of articles from academic journals commonly assigned on political science syllabi. Which active learning techniques are most effective for teaching students to recognize and evaluate social science evidence? To address this question, we conducted an experiment with students from two first-year writing seminars in political science. Students were randomly assigned to either an in-class writing activity or a group discussion, both of which required them to summarize an article's use of evidence. We find limited evidence that group discussions are more effective for teaching students to engage with evidence.